Assessing Institutional Readiness for Green Curriculum Implementation in Culinary Education - Luthfiyah Nurlaela; Aulia Bayu Yushila; Hidayatun Muyasyaroh; Mohd Yusof bin Kamaruzaman (International Journal of Pedagogy and Teacher Education, 2026)
Sustainability pressures within global food systems have intensified the need to integrate environmental principles into professional culinary training. While prior research has largely focused on student-level sustainability awareness, limited empirical attention has been given to institutional readiness for Green Curriculum implementation in applied vocational contexts. This study assesses institutional readiness for Green Curriculum implementation in university level culinary education. A descriptive quantitative survey design was employed involving 50 academic stakeholders. Four variables were examined and descriptive statistical analysis indicates very high endorsement of sustainability integration in curriculum design and instructional strategies (overall mean scores above 4.0 on a five point scale). However, ratings for supporting and constraining institutional (X4) conditions were comparatively lower (4.07). Sustainable ingredient availability (X4) emerged as the lowest rated item  (3.40), suggesting operational considerations in procurement and supply stability. Brief open-ended responses were used to contextualize these moderate ratings by highlighting concerns related to seasonal supply variability, cost instability, infrastructure readiness, and governance alignment. Overall, the findings reveal a readiness–constraint dynamic in which strong conceptual alignment coexists with structural and procurement-related limitations. This study provides a stakeholder-informed institutional mapping of feasibility conditions and implementation barriers to guide strategic Green Curriculum integration in culinary education